Voiles racialisés : la femme musulmane dans les imaginaires occidentaux - Al-Saji, Alia (Les ateliers de l'éthique, 2008)
Cet article étudie deux contextes français dans lesquels les voiles musulmans sont devenus hypervisibles : le débat public qui a mené à la loi française de 2004 interdisant les signes religieux ostensibles dans les écoles publiques, et le projet colonial français de dévoiler les femmes algériennes. Je montre comment le concept de « l’oppression de genre » s’est naturalisé au voile musulman d’une telle manière qu’il justifie les normes de féminités occidentales et cache le mécanisme par lequel les femmes musulmanes sont racialisées. C’est ainsi que le voile devient le point de mire d’un racisme culturel qui se présente comme libérant les femmes musulmanes, un racisme qui semble poser un dilemme au féminisme
Keywords: approches et analyses; corps; cours; discipline; droits des femmes*; europe; fem3400; femmes* musulmanes; france; histoire et politique; phi4336; philosophie; premier cycle; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis